The Effect of Research Evidence-Based Teaching Practices in Science Classrooms on Student Teachers' Attitudes towards Educational Research - Nail Ilhan (Universitas Pendidikan Indonesia, 2021)
Research in the field of education plays a pivotal role in developing evidence-based practices in teaching and improving the quality of education. However, research conducted in recent years has highlighted the unwillingness of teachers to benefit from scientific studies. This study set out to assess whether Research Evidence-Based Practices in Science Teaching (EBPST) influences the teaching practices of student teachers and their attitudes towards education research. Mixed methods research design was used in this study. The study was conducted through Quasi-experimental methods and focus group interviews. The data were collected with the